(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The urgency of the problem of chronic arterial hypertension (CAH) in pregnant women is due to an increase in the percentage of its prevalence and the severity of the consequences for the mother and fetus. Chronic hypertension occurs in about 3% of pregnant women and is the cause of an increased risk of the following complications during pregnancy: preeclampsia, fetal growth restriction, premature birth and stillbirth, and they account for 25-28% of the total number of complications that can occur in pregnant women with chronic arterial hypertension [1].